Association of Well-Being in Middle-Aged and Older Adults With Enhanced Personal Health and Social Support: A Nationally Representative Cohort Study - Ping-Chen Chung; Yen-Sheng Chiang; Yi-Chien Liu; Yi-Fang Chuang; Hsiao-Han Hsu; Ta-Chien Chan (SAGE Publishing, 2024)
Objectives: This study aimed to explore the relationship between multidimensional factors, such as environment, health status, behavior, social support, and the well-being of middle-aged and older adults. Methods: This study utilized data from 2 waves of the nationally representative Taiwan Longitudinal Study on Aging Survey Report (TLSA) conducted in 2015 and 2019. The TLSA assesses socioeconomic status, physical and health status, the 5-item World Health Organization Well-Being Index (WHO-5 index), and social support. Data regarding the degree of digital development were obtained from the 2020 Township Digital Development Report. We applied a generalized estimating equation (GEE) to analyze the influencing factors. Results: This study included 4796 participants. Residing in areas with a higher degree of digital development, having a higher socioeconomic status, and experiencing better physical and mental health were significantly associated with well-being. Furthermore, emotional and attentive support mediated the association between physical and mental status and well-being. Conclusion: People's awareness of searching for and receiving social support and medical resources is important for enhancing their well-being. It is also crucial to pay attention to the living environment and maintain one's health status to promote well-being.